A novel swab storage gel is superior to dry swab DNA collection, and enables long‐range high resolution next generation sequencing HLA typing from buccal cell samples. (6th April 2022) - Shimizu, Marie; Takahashi, Daisuke; Suzuki, Shingo; Shigenari, Atsuko; Ito, Sayaka; Miyata, Shigeki; Satake, Masahiro; Matsuhashi, Mika; Kulski, Jerzy K.; Murata, Makoto; Azuma, Fumihiro; Shiina, Takashi
Abstract : HLA sequence‐based DNA typing (SBT) by long‐range PCR amplification (LR PCR) and next‐generation sequencing (NGS) is a high‐throughput DNA sequencing method (LR‐NGS‐SBT) for the efficient and sensitive detection of novel and null HLA alleles to the field‐4 level of allelic resolution without phase ambiguity. However, the accuracy and reliability of the HLA typing results using buccal cells (BCs) and saliva as genetic source materials for the LR‐NGS‐SBT method are dependent largely on the quality of the extracted genomic DNA (gDNA) because a large degree of gDNA fragmentation can result in insufficient PCR amplification with the incorrect assignment of HLA alleles because of allele dropouts. In this study, we developed a new cost‐efficient swab storage gel (SSG) for wet swab collection of BCs (BC‐SSG) and evaluated its usefulness by performing different DNA analytical parameters including LR‐NGS‐SBT to compare the quality and quantity of gDNA extracted from BCs (in SSG or air dried), blood and saliva of 30 subjects. The BC‐SSG samples after 5 days of storage revealed qualitative and quantitative DNA values equivalent to that of blood and/or saliva and better than swabs that were only air‐dried (BC‐nSSG). Moreover, all the gDNA extracted from blood, saliva and BC‐SSG samples were HLA‐typed successfully to an equivalent total of 408 alleles for each sample type. Therefore, the application of BC‐SSG collection media for LR‐NGS‐SBT has benefits over BC dried samples (dry swabs) such as reducing retesting and the number of untestable BC samples because of insufficient DNA amplification.